The Fibrosis-4 Index Is Associated With Need for Mechanical Ventilation and 30-Day Mortality in Patients Admitted With Coronavirus Disease 2019. (28th August 2020) - Sterling, Richard K; Oakes, Tavis; Gal, Tamas S; Stevens, Michael P; deWit, Marjolein; Sanyal, Arun J
Abstract: The Fibrosis-4 Index (FIB-4), developed to predict fibrosis in liver disease, was used to identify patients with coronavirus disease 2019 who will require ventilator support as well as those associated with 30-day mortality. Multivariate analysis found obesity (odds ratio [OR], 4.5), diabetes mellitus (OR, 2.55), and FIB-4 ≥2.67 (OR, 3.09) independently associated with need for mechanical ventilation. When controlling for ventilator use, sex, and comorbid conditions, FIB-4 ≥2.67 was also associated with increased 30-day mortality (OR, 8.4 [95% confidence interval, 2.23–31.7]). Although it may not be measuring hepatic fibrosis, its components suggest that increases in FIB-4 may be reflecting systemic inflammation associated with poor outcomes. Abstract : The FIB-4 Index, a simple tool developed to predict hepatic fibrosis, was found to independently be associated with need for mechanical ventilation and 30-day mortality in hospitalized patients with COVID-19.